2019
DOI: 10.1103/physrevlett.123.180602
|View full text |Cite
|
Sign up to set email alerts
|

Collisional Quantum Thermometry

Abstract: We introduce a general framework for thermometry based on collisional models, where ancillas probe the temperature of the environment through an intermediary system. This allows for the generation of correlated ancillas even if they are initially independent. Using tools from parameter estimation theory, we show through a minimal qubit model that individual ancillas can already outperform the thermal Cramer-Rao bound. In addition, due to the steady-state nature of our model, when measured collectively the anci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
98
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 35 publications
1
98
0
Order By: Relevance
“…Outside of the steady state regime, it was found that access to the transient probe dynamics may outperform the steady-state protocols [19][20][21], that dynamical control acts as a resource [22][23][24], and that thermometry can in some cases be mapped to a phase estimation problem [25,26]. These findings have spurred further investigations into nonequilibrium thermometry [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Outside of the steady state regime, it was found that access to the transient probe dynamics may outperform the steady-state protocols [19][20][21], that dynamical control acts as a resource [22][23][24], and that thermometry can in some cases be mapped to a phase estimation problem [25,26]. These findings have spurred further investigations into nonequilibrium thermometry [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Thermometry makes part of the broader field of metrology [63][64][65][66] and aims at estimating the temperature of some environment at thermal equilibrium. In particular, temperature information can be transferred to a probe that undergoes a suitable coupling with the environment [67][68][69][70][71][72][73][74][75][76][77]. We show that this information can be increased via a two-level catalyst, thereby reducing the error in the temperature estimation.…”
Section: Introductionmentioning
confidence: 96%
“…Most of the current investigations in quantum thermometry use two-level systems as thermometers [8][9][10][11], shedding light on the link between the equilibrium heat capacity of such microscopic probes and the amount of information that can be gathered on the temperature of the environment [12][13][14], introducing bounds on the irreversible entropy production of the probe [15][16][17], and clarifying the extent of the advantages resulting from finite-time interactions for both temperature discrimination and estimation [14,18]. Such investigations have ultimately opened the path to the exploration of the role played by genuine quantum features in the enhancement of the thermometric performance of two-level quantum probes [19][20][21][22][23][24][25][26][27][28][29]. However, little has been explored about the effects that the dimensionality of the quantum probe has on the features of a given thermometric protocol.…”
Section: Introductionmentioning
confidence: 99%